Prevalence and Socio-demographic Correlates of Dental Phobia in Pakistani Adult Population - Sidra Afzal, Rubeena Zakar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental anxiety is a barrier to seeking dental treatment. Anxiety aggravates the pain and fear of the dental procedure. Dentists all over the world report dental anxiety and non-compliance toward dental procedures by their Patients. Objective: To find out the prevalence of dental anxiety in adults living in Lahore. Methods: A cross-sectional study was carried out to find out the prevalence of dental anxiety in adults. 1000 participants (Females 919, Males 81) with the age range of 18 to 60 years (M 32.18 SD 11.16) were selected. A modified dental Anxiety Scale along with a demographic Performa was given to the Participants. The participants were assessed in an individual setting. Results: the results of the study revealed that 4% of the participants fall under the mild category of dental phobia. 11 % had a moderate dental phobia, whereas 19 % of the participants had a high level of dental phobia. However, the majority of the participants suffer from severe levels of dental phobia i.e., 67%. The results of the Mann Whitney U analysis carried out showed that dental phobia was higher in females as compared to males (***p<.001). The results of one-way ANOVA showed that dental phobia was higher in uneducated adults as compared to educated adults (***p<.001). Conclusion: This study highlights the alarming prevalence rates of dental phobia that needs the attention of dental care providers to take preventative measures. The role of socio-demographic variables has implications for the timely assessment and management of dental phobia. Keywords: Dental phobia, Prevalence, Socio-demographic variables, Dental care (MeSH)